Middle and Late Jurassic radiolarians from the Neotethys suture in the Eastern Alps. (30th November 2016) - O'Dogherty, Luis; Goričan, Špela; Gawlick, Hans-Jürgen
Abstract: Cherty limestones, marls and radiolarites are widespread in the Hallstatt Mélange of the Northern Calcareous Alps. The mélange was formed during the Neotethyan orogeny in a series of deep-water basins that progressively developed in front of the advancing nappe front. The low thermal overprint of these rocks favors the good preservation of radiolarians (polycystines) that have been used for dating and reconstructing the Jurassic tectonostratigraphy of the area. This paper describes rich Middle–Late Jurassic radiolarian faunas from four localities in the Hallstatt Mélange near Bad Mitterndorf in Austria. Two different successions, both spanning from the Bathonian to the Oxfordian, are dated. In the first succession, the radiolarites are intercalated between or occur as matrix in mass-flow deposits originating from the accretionary wedge. The second succession is nearly 100 m thick but is devoid of mass-flow deposits and documents a continuous radiolarite deposition in greater distance from the nappe stack. Both successions are ascribed to the Sandlingalm Basin, which evolved on a relatively distal continental margin during early stages of the orogeny. The highly diverse and well-preserved radiolarian assemblages have been used for a detailed taxonomic study. Two new families are described : Minocapsidae n. fam. and Xitomitridae n. fam.; six new genera are described Doliocapsa n. gen., Crococapsa n. gen., Parvimitrella n. gen., Xitomitra n. gen., Campanomitra n. gen., and Mizukidella n. gen. In addition, one new replacement name, Takemuraella (pro Triversus ), is introduced, the diagnoses of 6 genera are emended, and two new species are described: Hemicryptocapsa nonaginta n. sp. and Mizukidella mokaensis n. sp.